2020
DOI: 10.1002/adhm.201901874
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Stem Cell Secretome Attenuates Inflammatory Response against Implanted Biomaterials

Abstract: Inflammatory response against implanted biomaterials impairs their functional integration and induces medical complications in the host's body. To suppress such immune responses, one approach is the administration of multiple drugs to halt inflammatory pathways. This challenges patient's adherence and can cause additional complications such as infection. Alternatively, biologics that regulate multiple inflammatory pathways are attractive agents in addressing the implants immune complications. Secretome of mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Hence, the function of hUCMSCs in promoting rapid vascularization at an early stage is vital to the retention of fat tissue. Also, the number of CD68 + macrophages associated with the severe degree of inflammatory response [ 39 ] in the tissue engineered breast was significantly reduced after hUCMSCs transplantation. This demonstrated that hUCMSCs could significantly reduce the number of CD68 + macrophages in the compound and impeded inflammatory responses, which consequently reduced the damage of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the function of hUCMSCs in promoting rapid vascularization at an early stage is vital to the retention of fat tissue. Also, the number of CD68 + macrophages associated with the severe degree of inflammatory response [ 39 ] in the tissue engineered breast was significantly reduced after hUCMSCs transplantation. This demonstrated that hUCMSCs could significantly reduce the number of CD68 + macrophages in the compound and impeded inflammatory responses, which consequently reduced the damage of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to its use as a bioink, alginate has been extensively explored as a culture system and delivery vehicle for MSCs in the fields of regenerative medicine and tissue engineering [ 68 72 ]. Alginate also plays a significant role in the controlled release of the paracrine factors derived from MSCs [ 71 , 73 , 74 ]. However, alginate offers poor biodegradability and cell adhesive properties, which limit its potential applications [ 67 , 70 ].…”
Section: Strategies For Improving the Therapeutic Effects Of Mscsmentioning
confidence: 99%
“…Various stem cell types, such as mesenchymal stem cells (MSCs), neural stem cells (NSCs), umbilical cord-derived blood stem cells (UCBs), and adipose-derived stem cells (ADSCs), have been used for therapeutics delivery toward cancer therapy with bone marrow-derived MSCs as the most common stem cell applied in cancer therapy studies . According to studies conducted so far, MSCs or their secretome are favorable for cancer treatment in mouse models of melanoma, oral cancers, cholangiocarcinoma, glioma, bladder cancer, and blocking inflammation in general . Also, MSCs have been genetically engineered to be used for carrying therapeutics to the tumor site. Notwithstanding, MSCs also have a pro-tumorigenic potential, as shown in some types of cancer cells.…”
Section: Applications Of Cell Encapsulation As Cellular Implantsmentioning
confidence: 99%
“…76 According to studies conducted so far, MSCs or their secretome are favorable for cancer treatment in mouse models of melanoma, 77 oral cancers, 78 cholangiocarcinoma, 79 glioma, 80 bladder cancer, 81 and blocking inflammation in general. 82 Also, MSCs have been genetically engineered to be used for carrying therapeutics to the tumor site. 83−86 Notwithstanding, MSCs also have a pro-tumorigenic potential, as shown in some types of cancer cells.…”
Section: Cellular Implants Formentioning
confidence: 99%